Association of waist-to-hip ratio with risk of kidney stones in hypertensive population: a population-based cross-sectional study - Zhang, Feiyan; Lv, Jie; Aibibula, Maidinaimu; Li, Jiahui; Ma, Xuechao; He, Yutong; Zhou, Haiyang (Frontiers in Endocrinology, 2025)
BackgroundKidney stones (KS) are a prevalent urological condition with high recurrence rates and substantial treatment costs. Hypertension has been identified as an independent risk factor for KS. The waist-to-hip ratio (WHR) has also been associated with KS; however, its relationship with KS in the hypertensive population remains unexplored. Through a population-based cross-sectional study, this study aimed to assess the association between WHR and KS risk in the hypertension population.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2007 to 2020 were analyzed, comprising 1,572 hypertensive patients. Logistic regression and restricted cubic splines analysis were performed to examine the association between WHR and KS. Receiver operator characteristic (ROC) analyses were performed to assess the diagnostic ability of several human obesity-related indices for KS.ResultsA total of 1,572 hypertensive patients were included in the final study, with a mean age of 54.87 years and a prevalence of KS of 12.28%. The study found a significant association between WHR and KS, even after adjusting for confounding factors, with higher WHR associated with a higher likelihood of KS occurrence (OR = 1.63, 95%CI: 1.13, 2.34). This positive association is linear (non-linear p >0.05). ROC curve results showed that WHR had the highest AUC. Subgroup analysis showed consistent associations in almost all populations, with no significant interaction effects (p for interaction > 0.05). Finally, sensitivity analysis further confirmed the stability of the results.ConclusionIn the hypertensive population, WHR is positively associated with the likelihood of KS. These findings highlight the importance of considering WHR as a risk factor for KS in hypertensive individuals, providing valuable insights for managing KS in this population.